INFLUENCE OF NI NANOPARTICLES ON GROWTH OF DLC FILM BY PECVD TECHNIQUE - KHALAJ, Zahra (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Plasma enhanced chemical vapor deposition (PECVD) technique is mostly used to fabricate diamond-like carbon (DLC) films on different type of substrate. Research on DLC films has been devoted to find both optimized conditions and characteristics of the deposited films on coated areas. In this work, the DLC films deposition on silicon coated Nickel layer were studied. Aluminum was used as a buffer layer, deposited directly on silicon at the room temperature. Atomic Force Microscopy was used to characterize the surface roughness and distribution function of the nickel nanoparticles. The DLC films quality was studied using Raman spectroscopy and Fourier transform infra-red spectroscopy (FTIR). The results show a lower intensity ratio of ID/IG for DLC films by increasing the Ni deposition time on the Si/Al/Ni substrates, providing a good quality of the DLC growth by increasing the nickel content and reducing the average roughness of the surface to less than 4 nm.